2021
DOI: 10.3390/jcm10040661
|View full text |Cite
|
Sign up to set email alerts
|

Same Day Discharge versus Inpatient Surgery for Robot-Assisted Radical Prostatectomy: A Comparative Study

Abstract: (1) Background: no study has compared outcomes of same day discharge (SDD) versus inpatient robot-assisted radical prostatectomy (RARP) in homogenous cohorts. Our aim was to compare perioperative outcomes and urinary continence recovery between SDD and inpatient RARP in contemporary, comparable patients. (2) Methods: we included consecutive patients undergoing RARP between 2018 and 2020 (n = 376). Only patients eligible for SDD (no oral anticoagulant, distance home-hospital <150 km) and having >6-month f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…In our study, although without reaching statistical significance, we observed an improvement in all peri‐operative outcomes in favour of PreHab+ vs PreHab− in the context of ERAS for all patients. The further development of programmes such as ERAS and PreHab could also translate into the wider implementation of same‐day discharge after RARP and could generate cost reductions at the hospital and healthcare system levels [14,24–26]. Another interesting point is that the mean length of stay in the present study was significantly shorter than the national statistics.…”
Section: Discussionmentioning
confidence: 75%
“…In our study, although without reaching statistical significance, we observed an improvement in all peri‐operative outcomes in favour of PreHab+ vs PreHab− in the context of ERAS for all patients. The further development of programmes such as ERAS and PreHab could also translate into the wider implementation of same‐day discharge after RARP and could generate cost reductions at the hospital and healthcare system levels [14,24–26]. Another interesting point is that the mean length of stay in the present study was significantly shorter than the national statistics.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, prehabilitation pathway along with ERPs and robotic surgery has also been suggested to work synergistically in improving outcomes after inpatient robotassisted radical prostatectomy (RARP), and to gain a wider acceptance of same day discharge (SDD), which is supposed to have a positive impact on pain control, general activity, and reduced overall costs. A multi-surgeon comparative study confirms the safety of routine SDD and RARP in terms of perioperative outcomes (32), trends favoring ERPs combined with prehabilitation, SSD and robotic surgery need to be confirmed, these improvements may promote high quality of life together for patients. Another two studies provided available data to support ERPs for patients undergoing radical cystectomy leading to a shorter LOS without increasing readmission or complication rates (33,34), suggesting more solid evidence of assessing the clinical and economic impact of ERPs.…”
Section: Discussionmentioning
confidence: 89%
“…There were 8 studies that reported on complication rates among 822 SDD RARPs (range 0%–24%) and 1,881 IP RARPs (2%–28.2%), 4–6,10,12,18–20 and meta-analysis favored lower overall complication rate in the SDD group (RR: 0.7, 95% CI 0.5,0.9, p=0.02; see supplementary Figure, https://www.urologypracticejournal.com). However, there was no difference in risk of ≥grade 3 CD complications (RR: 0.4, 95% CI 0.2, 1.1, p=0.07), 90-day readmission rates (RR: 0.6, 95% CI 0.3, 1.1, p=0.10) or unscheduled emergency department visits (RR: 1.0, 95% CI 0.3, 3.1, p=0.97).…”
Section: Resultsmentioning
confidence: 99%